Sustainable base-mediated chemical upcycling of poly (propylene carbonate) to β-hydroxy sulfides and oxides - Moyilla, Nageswararao; Padhi, Ganeshdev; Barsu, Nagaraju (Green Chemistry, 2025)
We present a cesium carbonate-mediated method to upcycle poly(propylene carbonate) (PPC) waste into beta-hydroxy sulfides, selenides, and phenoxides via selective thermal depolymerization. The process tolerates diverse nucleophiles, including those from multilayer plastics. Mechanistic studies support a cesium aryl thiolate-driven nucleophilic degradation. The beta-hydroxy products are easily functionalized, and the base is recyclable, offering a sustainable route for PPC valorization.